Impact of COVID-19 pandemic in dermatology outpatient visits - Fida, Monika; Toçi, Dorina; Toçi, Ervin; Dedej, Sabina; Tafica, Arbnore; Kore, Amanda; Vasili, Ermira (International Journal of Public Health Science (IJPHS), 2023)
The COVID-19 pandemic lockdown measures significantly affected the readiness of dermatology patients to contact health services. However, such trends have yet to be documented in Albania. To this aim, we collected the relevant information about all patients who sought medical help at the dermatology clinic, University Hospital Center “Mother Theresa”, in Tirana, Albania, during 2019-2021 and compared outpatient visits trend across the years. A total of 7,807 patients have been consulted in our dermatology clinic during this period. Compared to 2019, the number of visits decreased significantly by 72% in 2020 and 57% during 2021. The ratio of visits by gender Male/Female, for the three years, was 1:1.1, 1:1.3, and 1:1, respectively. The age group >65 years old had more frequently visited our clinic but its weight within all patients dropped by 5 percentage points during the pandemic. Patients from Tirana had frequented more often the outpatient unit in 2019 and 2021. In conclusion, the pandemic situation due to COVID-19 had an unprecedented impact on Dermatology Service in our university tertiary center. There were significant reductions in the number of outpatient visits, and other differences with regard to patients’ demographic characteristics.